Pauvreté et progrès technique en Amérique latine : une vue à long terme - Dudley, Leonard; Garcia, Norberto (L'Actualité économique, 1977)
AbstractThis study uses a simulation model of the Latin American economy in order to project the relationship between technical progress and income distribution over the 1970-2000 period. In the basic projections—an extrapolation of the present trends—a large number of urban and rural residents tend not to have access to the benefits of development. Alternative projections simulate the effects of policies aiming at i) the acceleration of growth, ii) the modification of the nature of technical progress, iii) the transfer of consumption. The impact of the two first policies is substantial, the main contribution of technological policies being a more equitable distribution of the benefits of growth.